Dinamika Keterlibatan Masyarakat dalam Pengembangan Fasilitas di Objek Wisata Pantai Cemara Sew - Fitria Nurmalita Sari (Gadjah Mada Journal of Tourism Studies, 2019)
This study aims at describing the involvement of the local community in developing facilities in Cemara Sewu Beach. Based on observations and interviews, it was found that the local community of Grogol VII were actively involved in providing facilities by contributing ideas, energy, and even materials such as money. Through the provision of these facilities, the community can obtain economic benefits, such as new jobs and business opportunities that can give them additional income.